FEATURES OF THE APPLICATION OF THE MODERN METHODOLOGICAL METHOD OF T-SHAPED TRAINING (EDUCATION IN THE 21ST CENTURY, 2023)
In the article entitled "Features of the application of the modern methodological technique of T-shaped learning", we tried to show the features of the application of this methodological technique, due to the nature of the taught material and the originality of the writer's image system, the age groups of students. We have considered several approaches to the application of the methodological technique..  The purpose of the article is to reveal, with the help of interesting observations, the essence of the above-mentioned methodological technique, the principles of teaching material in this format, indicating and justifying the advantages due to the relevant features of this teaching method, the features arising from the purpose of teaching.       The novelty of the research is the consideration of various approaches to the application of the modern methodological technique of T-shaped learning, their features. By the above-mentioned method, the symbols in the artwork were examined ; their philosophical and psychological layers were emphasized.      The relevance of the research determines the consideration of the process of teaching literary works by the requirements of modern teaching methodology, which makes it consonant with modern educational programs. In the article, we have demonstrated the effectiveness of using the modern methodological technique of T-shaped learning in various approaches, the possibility of using them for more meaningful and multi-level teaching of a work of art.               As a result of the research, we came to the following conclusions: the use of a T-shaped methodical technique contributes to a deeper analysis of the taught material, a comprehensive and comprehensive knowledge of the material by students, a broad presentation of the artwork, makes the lesson more interesting and meaningful.
Keywords: adviser; ideological issues; means of icon painting; philosophical layers